The Flexibility of Islamic Law in Responding to Climate Change Impacts on the Economy - Zahrah, Zahrah; Subli, Mohamad; Musyadat, Asep Anwar; Ni’amillah, Ni’amillah; Astuti, Widia (Al-'Aqdu: Journal of Islamic Economics Law, 2024)
This study aims to examine the flexibility of Islamic law in addressing the economic impacts of climate change, focusing on applying relevant Sharia principles in mitigating and adapting to these global challenges. It also analyzes how religious fatwas, such as MUI Fatwa No. 86 of 2023, and approaches by religious organizations like Nahdlatul Ulama and Muhammadiyah contribute to sustainable, Sharia-based solutions. This research employs a qualitative methodology with a juridical-normative approach. The primary sources include literature reviews of books, academic journals, religious fatwas, and official documents related to the flexibility of Islamic law, climate change impacts, and their economic implications. Data were analyzed to evaluate the relevance of Islamic law in providing adaptive solutions to contemporary issues. The findings reveal that the flexibility of Islamic law enables Sharia regulations to adapt to modern social and environmental conditions, including climate change. Principles such as maqasid al-shariah, maslahah mursalah, and usul al-fiqh have proven effective in supporting climate change mitigation and adaptation. Religious fatwas, such as MUI Fatwa No. 86 of 2023, along with the approaches of NU and Muhammadiyah, have significantly contributed to raising collective awareness and formulating environmental policies grounded in religious values. This study underscores the critical role of Islamic law in offering sustainable solutions that are both relevant and adaptive to the economic impacts of climate change.